PEMBERDAYAAN SANTRI PONDOK PESANTREN BABUSSALAM DAN AL MUQORROBIN MELALUI PELATIHAN KEWIRAUSAHAAN DAN BUDIDAYA SAYURAN ORGANIK DI KECAMATAN LAWANG KABUPATEN MALANG - Rahaju, Juli; Rahayu, Yekti Sri; Budi S, M. Adri; Esti, Erna Atiwi Jaya (PEDULI: Jurnal Ilmiah Pengabdian Pada Masyarakat, 2018)
Human resource potential and natural resources boarding school located in agricultural areas. It is an opportunity for the development of the boarding school in the field of agriculture. But the potential of land owned boarding school has not been explored to the optimum, due to the ability of students in the management of agricultural land is limited. The purpose of the implementation of Science and technology program for the community is to empower students in both Al Muqorrobin and Babussalam boarding school about entrepreneurship and develop the skills of the students in the field of organic farming. Methods of implementation of the program using a participatory approach groups or Participatory Rural appraisal (PRA), which involve the students in the education and training activities. Implementation results generally show that after following the extension of the entrepreneurial activities, the students that are interested in trying entrepreneurship particularly in the field of organic vegetables. After participating in the training, the students also have managed to cultivate vegetables and food crops both in the kitchen garden and land boarding school. Constraints faced especially in Babussalam boarding school, because of the location of water sources away from the land, making the maintenance activities so difficult. These problems can be solved by means of the addition of drainage water from the water well to the land. Recommendations on the implementation of this program is the continued assistance relating to the business plan for the students who will develop entrepreneurship in the field of organic farming .